The hybridization of vocational training and higher education in Austria, Germany, and Switzerland - Graf, Lukas [Verfasser] (Budrich UniPress, 2013)
"Austria, Germany, and Switzerland are increasingly relying on hybridization at the nexus of vocational training and higher education to increase permeability and reform their highly praised systems of collective skill formation. This historical and organizational institutionalist study compares these countries to trace the evolution of their skill regimes from the 1960s to today's era of Europeanization, focusing especially on the impact of the Bologna and Copenhagen processes." The key finding is that all three countries rely in part on "hybridization" - a specific combination of organizational and institutional elements from the two organizational fields of vocational education and training (VET) and higher education (HE) - to introduce gradual institutional reforms within their long-established skill formation systems. (Verlag, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; Berufsbildung; Hochschulbildung; Duales System; Dualer Studiengang; Berufsbildende höhere Schule; Höhere Berufsbildung; Institutionalismus; Europäische Integration; Europäischer Bildungsraum; Expertenbefragung; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz